2008
DOI: 10.1002/jbm.a.32059
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic electrospun polyurethane nanofiber matrices for hMSC culture in a microfluidic cell chip

Abstract: Mimicking cellular microenvironments by MEMS technology is one of the emerging research areas. Integrated biomimetic systems with nanofiber polymer networks and microfluidic chips were fabricated and cellular behaviors were observed by changing surface characteristics of nanofibers and flow rates of microchannels. Modification of polyurethane nanofiber surfaces were achieved by grafting acrylic acid with plasma treatment and these nanofiber matrices were employed in a poly(dimethylsiloxane) based microfluidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 28 publications
(29 reference statements)
1
25
0
Order By: Relevance
“…Another interesting work reported that nanofiber-based extracellular matrix proteins can be used for patterning substrates of hMSCs. 149 Various types of nanostructures can be engineered to mimic microenvironments using submicron sized synthetic nanofibers. It was observed that the cells on the AA-grafted nanofibers greatly promoted the hMSC adhesion, migration, and proliferation when compared to untreated nanofibers.…”
Section: Patterning Structuresmentioning
confidence: 99%
“…Another interesting work reported that nanofiber-based extracellular matrix proteins can be used for patterning substrates of hMSCs. 149 Various types of nanostructures can be engineered to mimic microenvironments using submicron sized synthetic nanofibers. It was observed that the cells on the AA-grafted nanofibers greatly promoted the hMSC adhesion, migration, and proliferation when compared to untreated nanofibers.…”
Section: Patterning Structuresmentioning
confidence: 99%
“…4, 15, 28 Although 2D cell culture matrices such as collagen and fibronectin layers have been widely applied in culture flasks and microfluidic devices, little research has been done to incorporate in vivo representative ECM analogue fibers in a fluidic device. 22 Cells and tissues are embedded within 3D, fibrous ECM in vivo , which have proven to be able to regulate cellular activities. 29 In other words, even under flow conditions, if cells are not cultured on an ECM analogue scaffold, they may not be able to fully mimic in vivo conditions.…”
Section: Resultsmentioning
confidence: 99%
“…There are few reports showing the integration of electrospun fibers in a fluidic device, all of which are based upon sealing a layer of electrospun fibers between a substrate (on which the fibers are first sprayed) and a channel slab. 21, 22 In addition, with these approaches the electrospun fibers only reside on one side of a square channel, which limits the area and capacity for cell culture, as well as the creation of a true 3D ECM scaffold. Moreover, some techniques used in these reports, such as nano-gold electrode array 21 add to the cost and complexity of the device.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is not favorable in cell culture applications in most of the experiments because cells needed to adhere to the substrate. To address this problem, chemical or electrochemical methods have been used to render such scaffolds hydrophilic [15][16][17]. Lee et al [15] used AA-grafted nanofibers to treat the electrospun polyurethane nanofiber matrices surface.…”
Section: Introductionmentioning
confidence: 99%
“…To address this problem, chemical or electrochemical methods have been used to render such scaffolds hydrophilic [15][16][17]. Lee et al [15] used AA-grafted nanofibers to treat the electrospun polyurethane nanofiber matrices surface. The results confirmed that the contact angle of the AA-grafted treated surface was 10 times smaller than the untreated ones.…”
Section: Introductionmentioning
confidence: 99%